2017
DOI: 10.3390/systems5030044
|View full text |Cite
|
Sign up to set email alerts
|

A Systems-Based Framework for Design and Analysis of an R and D Structure

Abstract: A critical challenge for managerial effectiveness and competitive advantage in research and development (R and D) organizations is developing an appropriate structural configuration. However, in finding an appropriate structural configuration, R and D managers are faced with unprecedented levels of uncertainty, ambiguity, and accelerating complexity, coupled with demands for increased productivity. This paper develops a systems-based framework to support rigorous design, analysis, and transformation of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In their application of a systems-based framework to the design, analysis, maintenance, and transformation of organizational structures of an R&D organization, Katina et al (2017) identified the need for complex systems design to provide balance among structural of design, control, and change. VSM is focused on two primary concerns with respect to system structure:…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their application of a systems-based framework to the design, analysis, maintenance, and transformation of organizational structures of an R&D organization, Katina et al (2017) identified the need for complex systems design to provide balance among structural of design, control, and change. VSM is focused on two primary concerns with respect to system structure:…”
Section: Discussionmentioning
confidence: 99%
“…(1) the arrangement of the structural components that perform system functions and (2) the flow of information necessary to maintain essential relationships among the components. Katina et al (2017) suggest that system design (or redesign in this case) be based on a clear understanding of system operation functions (products, services, or information) and the "fit" with the environment. The insights developed by Katina et al (2017) in R&D system design could be readily adapted to re-design of the US Navy's IT systems governance:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations